Autolimbal Transplantation and Two-component Autofibrin Glue in the Treatment of Repeatedly Recurrent Pterygium - Yu. V. Kozlova; S. V. Churashov; A. N. Kulikov; A. Yu. Malafeeva; V. V. Karpovich; A. G. Ianushko (Oftalʹmologiâ, 2025)
We have proposed a method for fixing an autolimbal graft using a two-component autofibrin glue. The use of this adhesive composition is justified by the formation for strong adhesion and tissues fixation, as well as the relief of local inflammatory reaction due to the platelet-rich plasma (PRP) included in its composition.Objective. To compare the effectiveness of autolimbal transplantation using a two-component autofibrin glue and suture fixation in multiple recurring pterygium over a two-year follow-up period.Patients and methods. The study included 19 patients (20 eyes) with repeatedly recurring pterygium. The autolimbal graft was fixed using two-component autofibrin glue in the study group and using suture material (10/0 silk) in the control group. Using optical coherence tomography of the anterior segment, we assessed the adaptation of the graft in the bed and used a questionnaire to analyze the degree of discomfort in the postoperative period. A comparative analysis of the operation’s duration, epithelialization, and rehabilitation period was performed between the study groups, and cases of pterygium recurrence were recorded throughout the entire observation period (2 years).Results. A comparative analysis of the effectiveness of various methods of autolimbal graft fixation revealed a statistically significant reduction in the operation’s duration, the time to achieve complete epithelialization, and rehabilitation using two-component autofibrin glue. A lower level of discomfort in the postoperative period was noted in the study group. During two years of observation, 1 case of pterygium recurrence was recorded in each group.Conclusion. The advantages of using an adhesive composition for fixing an autolimbal transplant are the low level of surgical trauma and rapid rehabilitation of patients. Two-component autofibrin glue can act as a full-fledged replacement for the suture method of tissue fixation in the treatment of repeatedly recurring pterygium.